Adaptation, mitigation and 'green' R&D to combat global climate change: Insights from an empirical integrated assessment exercise - Francesco Bosello (Fondazione Eni Enrico Mattei (FEEM), 2010)
This work develops a framework for the analysis at the macro-level of the relationship between adaptation and mitigation policies. The FEEM-RICE growth model with stock pollution, endogenous R&D investment and emission abatement is enriched with a planned-adaptation module where a defensive capital stock is built through adaptation investment. Within this framework the optimal path of planned adaptation, the optimal inter and intra temporal mix between adaptation, mitigation and investment in R&D, and the sensitivity of a strategy to each other is identified. The major conclusions of this research show that adaptation, mitigation and R&D are strategic complements as all concur together to the solution of the climate change problem; nonetheless the possibility to adapt reduces the need to mitigate and partly crowds out other forms of investment like those in R&D. The optimal intertemporal distribution of strategies is also described: it requires to anticipate mitigation effort that should start already when climate damages are low and postpone adaptation intervention until they are substantial. Thus the possibility to adapt is not a justification to delay abatement activities. A sensitivity analysis demonstrates the robustness of these results to different parameterizations, in particular to changes in expected climate-change damages and in the discount rates.
Keywords: Q25; Q28; 330; Climate Change Impacts; Mitigation; Adaptation; Integrated Assessment; Klimaveränderung; Klimaschutz; Umweltpolitik